Coming together for tomorrow - Abd Razak, Dzulkifli (2009)
THE cabinet lineup announced recently is yet another clear commitment by the government to the future of education in Malaysia. The appointment of the deputy prime minister to the Education Ministry is a firm endorsement that education will continue to ride the crest of change to shape the nation's future. There can be no better person than the deputy prime minister himself, Tan Sri Muhyiddin Yassin, to look into the vital issues to help future generations of Malaysians to be even more cohesive in leading the nation into a progressive and prosperous era.